2012
DOI: 10.1179/1743288x12y.0000000024
|View full text |Cite
|
Sign up to set email alerts
|

Hydrotherapy in the management of chronic obstructive pulmonary disease: a qualitative systematic review

Abstract: Background: Many people worldwide suffer from chronic obstructive pulmonary disease (COPD). Diverse medical conditions have been treated using hydrotherapy for many years but its use in the treatment of COPD is a recent development. Its use in the COPD population may lead to improvements in cardiopulmonary outcomes and quality of life (QoL) and the mastery of activities of daily living (ADL) in people with this disease. Objectives: To determine the effects of hydrotherapy on cardiopulmonary function, QoL, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Due to the load of water exercise on the respiratory muscles, there may be a significantly positive effect on their strength [2,16]. Five studies assessed respiratory muscle strength using MIP and MEP [22,23,[25][26][27], and only the study by [27] found no improvement in either group; the remaining studies showed improvement in both the WE and the LE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the load of water exercise on the respiratory muscles, there may be a significantly positive effect on their strength [2,16]. Five studies assessed respiratory muscle strength using MIP and MEP [22,23,[25][26][27], and only the study by [27] found no improvement in either group; the remaining studies showed improvement in both the WE and the LE.…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic WE, thanks to the loading effect on respiratory muscles, may also benefit lung function, dyspnea and respiratory muscle strength in COPD patients [2,4,16,17]. However, the meta-analysis by [3] suggests that there may be no significant differences between LE or WE in terms of exercise capacity or pulmonary function improvement [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in studies based on aerobic exercise in different water and land environments, exercise capacity showed different performance in the outcome index [8,19] . For example, the results of Shead and Aswegen [18] and McNamara et al [16] found that ESWT was significantly increased in both water and land groups, but the results of ISWT were particularly different. These studies show contradictory results, which may be due to the included study, the frequency, time and content of the intervention, and the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive dyspnea can lead to fatigue, [40] prevent physical exercise, and reduce the functional level of patients. [9] Studies found that after aerobic exercise intervention combined with respiratory muscle and auxiliary muscle stretching, [41,42] the dyspnea of COPD patients decreased, the respiratory efficiency needed for ventilation increased, [18] and upper limb fatigue was significantly improved. [42] We observed that the dyspnea level of patients in the aerobic training group decreased significantly by 0.70 (95% CI:-1.12, -0.27).…”
Section: Comparison Between Groupsmentioning
confidence: 99%
See 1 more Smart Citation